Risk Sharing in Currency Unions: The Migration Channel - Wilhelm Kohler; Gernot Müller; Susanne Wellmann (Center for Economic Studies and Ifo Institute (CESifo), 2021)
Country-specific business cycle fluctuations are potentially very costly for member states of currency unions because they lack monetary autonomy. The actual costs depend on the extent to which consumption is shielded from these fluctuations and thus on the extent of risk sharing across member states. The literature to date has focused on financial and credit markets as well as on transfer schemes as channels of risk sharing. In this paper, we show how the standard approach to quantify risk sharing can be extended to account for migration as an additional channel of cross-country risk sharing. In theory, migration should play a key role when it comes to insulating per capita consumption from aggregate fluctuations, and our estimates show that it does so indeed for US states, but not for the members of the Euro area (EA). Consistent with these results, we also present survey evidence which shows that migration rates are about 20 times higher in the US. Lastly, we find, in line with earlier work, that risk sharing is generally much more limited across EA members.
Keywords: F41; F22; G15; J61; 330; risk sharing; currency unions; labour migration; migration rates; Euro area